2021
DOI: 10.3390/ijms222413459
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Regulation of Obesity

Abstract: Obesity has now reached pandemic proportions and represents a major socioeconomic and health problem in our societies [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…None showed significant changes, indicating the absence of peripheral inflammation. It has been reported that inflammation in the hypothalamus, the part of the brain responsible for regulating appetite and metabolism, can lead to an increased appetite and decreased energy expenditure, resulting in weight gain [ 28 , 29 , 30 ], a condition known as “hypothalamic obesity”. Based on this, we investigated the association between hypothalamic inflammation and body weight gain in CST cKO mice.…”
Section: Resultsmentioning
confidence: 99%
“…None showed significant changes, indicating the absence of peripheral inflammation. It has been reported that inflammation in the hypothalamus, the part of the brain responsible for regulating appetite and metabolism, can lead to an increased appetite and decreased energy expenditure, resulting in weight gain [ 28 , 29 , 30 ], a condition known as “hypothalamic obesity”. Based on this, we investigated the association between hypothalamic inflammation and body weight gain in CST cKO mice.…”
Section: Resultsmentioning
confidence: 99%
“…An imbalance between the energy in and the energy out can directly induce the excessive accumulation of fat [ 21 ]. We found that the fat masses of both the epididymal white adipose tissue (eWAT) and perirenal white adipose tissue (pWAT) in the TRIM67 KO mice were heavier than those in the WT mice under HFD exposure ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…We observed associations among the striatum, hypothalamus, and cortical cells. The striatum plays an important role in reward processing [67], and the hypothalamus is involved in hormone and nutrient sensing, which maintains body weight, food intake, and energy expenditure [68]. Altered hypothalamic function is related to the dysfunction of the inhibitory circuit, inducing hedonic eating [69].…”
Section: Discussionmentioning
confidence: 99%